Influência da morfologia e do cisalhamento na produção de enzimas celulolíticas por Aspergillus niger - Buffo, Mariane Molina (2020)
Issues related to sustainability and development of renewable and less polluting processes are increasingly in evidence, due to the various environmental crises and a greater concern with the scarcity of non-renewable resources, such as oil. Therefore, a bio-based world economy is emerging in response to the global and environmental challenges. An example of a bio-based product are cellulolytic enzymes. This enzymes are produced mainly by filamentous fungi Trichoderma and Aspergillus. Such enzymes are important in several industrial sectors, how for example in the production of second generation ethanol, another important product of biological basis, renewable and environmentally friendly since it uses agro-industrial waste in its manufacture. However, one of the bottlenecks in the production of second generation ethanol, which makes it still uncompetitive compared to first generation ethanol and petrol oil, is the high cost of cellulolytic enzymes. The present thesis studied two important variables related to the production of cellulolytic enzymes, cell morphology and shear conditions, in an attempt to improve the production of cellulite enzymes by A.niger in bioreactors. The shear suffered by A.niger was quantified through the fragmentation suffered by the microorganism’s pellets in different bioreactors, impellers and operating conditions. Through image analysis and measurements of the average diameter of the pellets over time it was possible to propose a kinetics for the pellet fragmentation. The fragmentation of the pellets was mainly dependent on the type of bioreactor and the agitation speed. The airlift bioreactor was less harmful to the microorganism and higher agitation speeds took to more abrupt fragmentation. The shear kinetic parameters were directly related to the production of cellulolytic enzymes, with lower shear conditions favoring the production of endoglucanase and more intense conditions producing β-glucosidase. Regarding with the morphology, a technique of concomitant change of pH and spore concentration in the inoculum was successfully used to obtain different morphologies of A. niger, since larger pellets to almost completely dispersed morphology. Such morphological change was quantified through a proposed morphological parameter, which considered the frequency of each morphological class and a form factor that represents a characteristic dimension of each morphological form. The measures were possible through image treatment of the filamentous fungi, the images were obtained under a microscope and stereoscope using specific software to be treats. Inoculums with morphologies of pellets, clumps and dispersed were then tested in the production of cellulolytic enzymes, and a greater production of endoglucanase was obtained with inoculum in the pelletized form, value approximately three times higher when compared to dispersed morphology, for shaker results. In oposite a greater production of β-glucosidase was obtained with inoculum in the dispersed form, this value is four times higher in the flask assays and 160% higher in the bioreactors.Such results show the importance of the shear and morphology variables in the production of cellulolytic enzymes by A. niger and how such influences may be different, depending on the metabolite under study.